THE EFFECT OF PROVIDING GENDER EQUALITY IN THE FAMILY ENVIRONMENT ON YOUTH'S CULTURE OF INTERACTION (TAMADDUN NURI JURNALI, 2024)
This article presents information about the impact of ensuring gender equality in the family environment on the behavior culture of young people. Modern approaches to ensuring gender equality in the family environment are also analyzed.